Enhanced visualization of influenza A virus entry into living cells using virus-view atomic force microscopy - Aiko Yoshida; Yoshitsugu Uekusa; Takeshi Suzuki; Michael Bauer; Nobuaki Sakai; Yohei Yamauchi (Proceedings of the National Academy of Sciences, 2025)
Influenza A virus (IAV) entry into host cells begins with interactions between the viral envelope proteins hemagglutinin (HA)/neuraminidase (NA) and sialic acid moieties on the cell plasma membrane. These interactions drive IAV’s lateral diffusion along the cell membrane and trigger membrane morphological changes required for endocytosis. However, directly visualizing these dynamic processes, which are crucial for IAV entry, has been challenging using conventional microscopy techniques. In this study, we enabled live-cell observation of nanoscale morphological dynamics of IAV and the cell membrane by reducing the mechanical invasiveness of atomic force microscopy (AFM). A customised cantilever with less than half the spring constant of conventional cantilevers enabled virus-view AFM imaging that preserved IAV–membrane interactions. By combining virus-view AFM with confocal microscopy, we performed correlative morphological and fluorescence observations of IAV lateral diffusion and endocytosis in living cells. Variations in diffusion coefficients of single virions suggested heterogeneity in sialic acid density on the cell membrane. NA inhibition decreased diffusion coefficients, while reduced sialic acid density increased them. The timing of clathrin accumulation at virion binding sites coincided with a decrease in diffusion coefficients, a relationship that was maintained independent of NA activity or sialic acid density. As clathrin assembly progressed, ~100-nm-high membrane bulges emerged adjacent to the virus, culminating in the complete membrane envelopment of the virus at peak clathrin accumulation. Our virus-view AFM will deepen our understanding of various virus–cell interactions, facilitate the evaluation of drug effects and promote future translational research.